2022
DOI: 10.21776/ub.jtsl.2022.009.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Application of Compost With Inorganic Fertilizer on Population of Phosphate-Solubilizing Bacteria and Maize Yield in Dry Land

Abstract: The aim of this study was to explore the effect of a combination of manure and inorganic fertilizer (NPK and Urea) on the population of phosphate-solubilizing bacteria and the yield of maize. The study was carried out from June to October 2018 in the Kemantren Village, Alas Kulak Hamlet, Jabung District, Malang Regency. This study used a randomized block design consisting of 8 treatment levels and repeated three times. The results of the analysis of variance showed that the application of a combination of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The inorganic variant is a type of chemical fertilizer that is widely used because it is easily obtained and has a positive impact on plant growth as well as productivity. However, dependence on their usage can cause damage to the environment [ 5 , 6 ]. A previous study [ 7 ] revealed that consistent use of inorganic fertilizers can cause a decrease in soil fertility, thus reducing its carrying capacity for plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic variant is a type of chemical fertilizer that is widely used because it is easily obtained and has a positive impact on plant growth as well as productivity. However, dependence on their usage can cause damage to the environment [ 5 , 6 ]. A previous study [ 7 ] revealed that consistent use of inorganic fertilizers can cause a decrease in soil fertility, thus reducing its carrying capacity for plant growth.…”
Section: Introductionmentioning
confidence: 99%